Continuing education - Griffin, Joyce A. (The Hastings Center report, 2013)
Working at The Hastings Center has been a tremendous professional stepping stone for me. I have long wanted to work in publishing, and I'm leaving the Center to work for America's oldest publisher, John Wiley and Sons. But I feel that my time here has been more than that-that it has truly continued my education in ways I could not have anticipated. Thank you for letting me be part of your intellectual lives.